PENYULUHAN UMKM DENGAN METODE DIVERSIFIKASI PADA PRODUK MAKANAN OLAHAN DENGAN PENAMBAHAN VARIAN RASA BARU DAN DESAIN PRODUK DI DESA TANJUNG SARI KECAMATAN PABUARAN KABUPATEN SERANG - Ita Rosita Wahyiah; Luis Fiska Rahayu; Eli Apud Saepudin; Mohamad Ikrom Arasid; Suherman Arifin; Tubagus Bagas Adya Wijaya Kusuma; Jesika Anastasya Simarmata (Indonesian Collaboration Journal of Community Services (ICJCS), 2023)
Product development is an activity carried out by companies or business people to perfect their products, one of the aims of product development is to increase sales volume. Through the PKM program, it is carried out by providing direct counseling and assistance to MSME actors in Tanjungsari Village, District. Pabuaran. The method used is implementation through material delivery seminars, discussions, practice with direct product processing and adding new innovations to processed emping melinjo food products as well as product packaging by adding product designs to processed emping melinjo food products, direct assistance, monitoring and evaluation . The results obtained were that the PKM ran smoothly and was participated enthusiastically by all craftsmen. After the craftsmen have attended training, the products have attractive designs and packaging, have an understanding of the manufacture and use of e-commerce, the products are widely known and liked by consumers and turnover has increased significantly